2018
DOI: 10.2147/cmar.s179368
|View full text |Cite
|
Sign up to set email alerts
|

Palliative gastrectomy plus chemotherapy versus chemotherapy alone for incurable advanced gastric cancer: a meta-analysis

Abstract: BackgroundWhether palliative gastrectomy combined with chemotherapy can improve the survival of patients with advanced gastric cancer remains controversial. We performed a meta-analysis to clarify whether palliative gastrectomy plus chemotherapy can benefit patients with incurable advanced gastric cancer and to explore the best candidates in this patient population.MethodsWe searched the literature systematically using electronic databases including PubMed, EMBASE, and the Cochrane Library. And HRs and their 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
2
4
0
Order By: Relevance
“…More importantly, survival analysis showed that patients treated with HIFU had the best OS and PFS, followed by PC, while the BSC group had the worst survival rate. The median survival time in the BSC group was about half a year, which is in line with previous studies [ 42 , 43 ]. The median survival time of the patients who underwent PC was about twice as long as that of the BSC group, up to approximately 1 year.…”
Section: Discussionsupporting
confidence: 92%
“…More importantly, survival analysis showed that patients treated with HIFU had the best OS and PFS, followed by PC, while the BSC group had the worst survival rate. The median survival time in the BSC group was about half a year, which is in line with previous studies [ 42 , 43 ]. The median survival time of the patients who underwent PC was about twice as long as that of the BSC group, up to approximately 1 year.…”
Section: Discussionsupporting
confidence: 92%
“…More importantly, survival analysis showed that patients treated with HIFU had the best OS and PFS, followed by PC, while the BSC group had the worst survival rate. The median survival time in the BSC group was about half a year, which is in line with previous studies [42,43]. The median survival time of the patients who underwent PC was about twice as long as that of the BSC group, up to approximately 1 year.…”
Section: Discussionsupporting
confidence: 91%
“…Although Katai et al [10] reported nonideal short-term survival after surgery in elderly patients ten years ago, some recent studies have demonstrated that the postoperative morbidity and mortality in elderly patients are comparable with those in younger patients [19,22], which may be attributable to advances in nutritional support, anesthesia, surgical instruments and skills. The benefits of surgery plus CT for the survival of GC patients with stage IV disease were also clearly identified [12,26,27,32]. The postoperative complication rate was not different between elderly populations of different ages, which suggested that the benefits of surgical intervention would not decrease with age.…”
Section: Discussionmentioning
confidence: 87%